Lycopene intake and prostate cancer risk in men at high cardiovascular risk: a prospective cohort study - López‑Solís, Ricardo; Castro‑Barquero, Sara; Donat‑Vargas, Carolina; Corrado, Marina; Arancibia‑Riveros, Camila; Martínez González, Miguel Ángel; Salas-Salvadó, Jordi; Sorlí, José V.; Serra‑Majem, Luis; Fitó, Montserrat; Pintó, Xavier; Fiol, Miquel; et al. (Springer Nature, 2025)
Intake of lycopene has been proposed as a protective dietary factor against prostate cancer development. Cardiovascular disease and prostate cancer share risk factors, which may modulate the effect of lycopene in high-risk individuals. This study aimed to examine the association between lycopene intake and prostate cancer risk in a Mediterranean population at high cardiovascular risk. A prospective cohort analysis was conducted among 2970 men aged 55-80 years at high cardiovascular risk from the PREDIMED trial, a multicenter study in Spain. Lycopene intake was assessed using repeated food frequency questionnaires. Prostate cancer cases were identified through medical records and death certificates. Cox proportional hazard models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) across lycopene intake quartiles. Over a mean follow-up of 5.8 years, 104 prostate cancer cases were identified. Participants in the highest quartile of lycopene intake had a significantly lower risk of prostate cancer than those in the lowest quartile (HR: 0.46; 95% CI: 0.23-0.95; p-trend = 0.035). A nonlinear dose-response relationship was observed, with a significant inverse association emerging at intakes above 4.9 mg/day (HR: 0.36; 95% CI: 0.13-0.98). Higher lycopene intake suggested a protective association with a lower incidence of prostate cancer in men at high cardiovascular risk. These findings support the role of lycopene-rich diets in prostate cancer prevention, which may be particularly relevant for high cardiovascular risk populations.
Keywords: Próstata - Cáncer - Prevención; Lycopene; Prostate cancer; Nutrition; Cancer prevention; Cardiovascular risk